Attenuated phase shift masks: a wild card resolution enhancement for extreme ultraviolet lithography? - Erdmann, Andreas; Mesilhy, Hazem; Evanschitzky, Peter (Journal of Micro-Nanolithography MEMS and MOEMS, 2022)
Background: The successful introduction of extreme ultraviolet (EUV) lithography to high volume manufacturing has increased the interest to push this technology to its ultimate limits. This will require photoresist materials, which enable a better tradeoff between resolution, linewidth roughness and sensitivity, and the adaptation of optical resolution enhancements that were originally developed for deep ultraviolet (DUV) lithography.
CRIS-Team WoS Importer:2022-08-12